Unfolding narrative meaning over time: The contributions of mother–daughter conversations of difficulty on daughter narrative sense-making and well-being. Issue 3 (2nd July 2016) - Horstman, Haley Kranstuber; Maliski, Ryan; Hays, Alexie; Cox, Joy; Enderle, Amy; Nelson, Leslie R.
ABSTRACT: Recent narrative theorizing suggests that humans process their difficult experiences by not only creating stories—called individual narrative sense-making (NSM)—but also by telling those stories with others—called communicated narrative sense-making (CNSM). The present study investigated the relationship between individual and communicated NSM to understand the effects of interpersonal communication on intrapersonal meaning-making and well-being. In this longitudinal, laboratory-based study, 62 mother–daughter pairs wrote and discussed stories of daughters' difficulty. Findings revealed that CNSM—particularly turn-taking, coherence, and daughters' perspective-taking—predicted increased positivity in daughters' stories over time, suggesting that CNSM contributes to "re-authoring" of individual stories. Limited effects emerged for CNSM and well-being. Findings expanded knowledge about the interconnections between intrapersonal and interpersonal communication, and well-being.